EFEKTIVITAS PROGRAM KREDIT USAHA RAKYAT DI KOTA YOGYAKARTA: Studi pada Pelaksanaan Program Kredit Usaha Rakyat di BRI Cabang Yogyakarta Tahun 2008-2010 - , DHITA FITRI ASTUTI; , Ario Wicaksono, SIP, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Micro, Small and Medium Enterprises (MSMEs) have a big potential in the national economic of Indonesia. But thereâs a lot of obstacles that faced by MSMEs to keep their business on, one of them is the capital issued where MSMEs has a difficulty to access bank finance, even though the accessibility of bank loans is vital for MSMEs to develop their business. On the other hand, banks are still having difficulties to be able to provide credit to SMEs, because in generally MSMEs have been feasible, but not yet bankable. To solve the problem, government then issued a program Kredit Usaha Rakyat (KUR) on 5 November 2007. Conceptually, these loans do not require collateral in lending as credit is given to MSMEs that considered viable, PT. Asuransi Kredit Indonesia (Askrindo) and Perum Sarana pengembangan Usaha (SPU) was appointed as the KUR guarantor. This study aims to determine the effectiveness of the program's Kredit Usaha Rakyat (KUR) carried out by the Bank Rakyat Indonesia in Yogyakarta, also to investigate the factors that influence the effectiveness of the program. The research method used in this research is a qualitative research method using a descriptive approach. Meanwhile, the source of the data obtained from the study of the Yogyakarta branch BRI, interviews with people who use the client program BRI KUR in Yogyakarta branch, as well as from documents related to the research focus of the KUR program effectiveness. From the data analysis it can be concluded that the implementation of the KUR program was less effective, because KUR only able to fulfill the objectives of the program, which provides ease of access to credit for MSMEs which includes credit application requirements, processes and procedures for filing, and loan disbursement time quite brief. While the accuracy of the program to reach the target group, KUR considered ineffective because the program can still be used by the group that is not a target of the program, where the procedure is intended for businesses KUR feasible and not bankable, and for new venture that has never been accessing credit. But in the implementation, many customers who already have access to credit can still access the KUR program where the customer actually has bankable. Keywords: effectiveness, credit, MSME, KUR